2013
DOI: 10.1200/jco.2013.31.4_suppl.546
|View full text |Cite
|
Sign up to set email alerts
|

Tumor size as a prognostic factor for patients with colon cancer undergoing sentinel lymph node mapping and conventional surgery.

Abstract: 546 Background: Unlike other solid tumors, tumor size (TS) is not a part of the TNM staging for colon cancer (CC). Our goal is to correlate TS with TNM staging, nodal positivity(NP), and 5-year overall survival (OS) for patients (pts) with invasive CC undergoing sentinel lymph node mapping (SLNM) vs. conventional surgery (CS). Methods: A retrospective review of 681 pts with invasive CC were reviewed and divided into two groups of pts (SLNM and CS). The pts in these two groups were subdivided according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Our study is supported by several previous studies (10)(11)(12)21). Saha et al (11) examined the role of tumor size in a large retrospective analysis of 300,386 patients and reported that tumor size was positively associated with important prognostic factors (such as T stage and N stage) and had negative impact on survival.…”
Section: The Seer Cohortsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study is supported by several previous studies (10)(11)(12)21). Saha et al (11) examined the role of tumor size in a large retrospective analysis of 300,386 patients and reported that tumor size was positively associated with important prognostic factors (such as T stage and N stage) and had negative impact on survival.…”
Section: The Seer Cohortsupporting
confidence: 89%
“…Theoretically, tumor size ought to serve as a key predictor of treatment response and prognosis. While tumor size has been shown to have prognostic value in stage II and III CRC (10)(11)(12), its value in stage IV CRC is not yet established.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, right-sided CRC is frequently diagnosed at a later stage, with the tumor size being larger, due to the capacious nature of the proximal colon (47). It is well known that the tumor size and depth of invasion (58) correlates with prognosis and overall survival rate of primary CRC patients (59).…”
Section: Il-38 and Crcmentioning
confidence: 99%
“…Previous studies showed that age at diagnosis, 3 , 6 9 tumor grade, 4 , 10 , 11 and tumor size 5 , 12 , 13 had a strong correlation with the prognosis of colon cancer. For example, Saha et al 13 found that the 5-year overall survival was 66%, 52%, 46%, and 41% in the subgroups with tumor sizes of 0–2, >2–4, >4–6, and >6 cm, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, many subsequent studies revealed that age at diagnosis, 6 9 tumor grade, 10 , 11 and tumor size 12 , 13 had a strong correlation with the prognosis of colon cancer. Yet most of them focus on the prognostic significance of one single factor and no study attempt to combine the three factors together for improved prognostic prediction.…”
Section: Introductionmentioning
confidence: 99%